ANALISIS SEMIOTIKA CHARLES SANDERS PEIRCE DALAM PUISI “KI HAJAR DEWANTAR “ KARYA SANUSI PANE - Sihombing, Rika Chintia; Hanna Geovanni Tampubolon; Mei Pitriani Manurung (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
To explore the semiotics of Charles Sanders Peirce found in Sanusi Pane’s poetry Ki Hajar Dewantara, the researcher utilizes a hermeneutic approach and qualitative method. In particular, this study looks at the meanings of symbols, icons, and indices as part of Peirce's trichotomy of signs, where indices are based on cause-and-effect relationships (like "you are an educator") and icons are based on resemblance (like "dawn," which represents the nation's enlightenment). In this poem, Ki Hajar Dewantara is portrayed as a patriotic and educational character who instills humanity, struggle, and nationalism in Indonesian society through free education and resistance to colonial oppression. The application of Peircean semiotics to uncover diction, figurative language, and rhythm—poetic characteristics that aid interpretation—is the emphasis of the research. Each verse contains indicators that relate education with patriotism and symbols such as “your tongue is sharp,” which signifies social criticism and opposition. Ten symbols that highlight Ki Hajar's function as a guide to national awareness are also identified by our investigation. These components work well together to interpret the patriotic and educational messages, exposing Sanusi Pane's nationalist worldview as an homage to Ki Hajar, the first Minister of Education who established the Republic of Indonesia. According to other sources, Sanusi Pane's poems—including this ode—are considered an appreciation of Ki Hajar's character education ideals, which highlight the significance of unselfish struggle and their applicability to the canonization of national literature. This semiotic approach increases Indonesian literary comprehension by unearthing thoughts about nationalism and the struggle for independence. Therefore, semiotic analysis promotes the appreciation of Indonesian literature, which is relevant for language instruction in universities such as HKBP Nommensen University, and assists in grasping hidden meanings in contemporary literary works.